2020
DOI: 10.1002/alz.12133
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for overall survival in sporadic Creutzfeldt‐Jakob disease

Abstract: Introduction: We developed a prognostic model for overall survival after diagnosis of sporadic Creutzfeldt-Jakob disease (sCJD) using data from a German surveillance study. Methods: We included 1226 sCJD cases (median age 66 years, range 19-89 years; 56.8% women with information on age, sex, codon 129 genotype, 14-3-3 in the cerebrospinal fluid (CSF), and CSF tau concentrations. The prognostic accuracy for overall survival was measured by the c statistics of multivariable Cox proportional hazard models. A scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
1
30
1
1
Order By: Relevance
“…66 CSF t-Tau has also become a candidate as predictor of survival time. 67 The p-Tau/t-Tau (or t-Tau/p-Tau) ratio is a very important alternative biomarker for sCJD. 66 It showed a very high diagnostic accuracy in the differentiation of sCJD from other neurological diseases (OND, AUC: 0•98), AD (AUC 0•99), 68 and rapidly progressive AD (AUC 0•99).…”
Section: Tau Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…66 CSF t-Tau has also become a candidate as predictor of survival time. 67 The p-Tau/t-Tau (or t-Tau/p-Tau) ratio is a very important alternative biomarker for sCJD. 66 It showed a very high diagnostic accuracy in the differentiation of sCJD from other neurological diseases (OND, AUC: 0•98), AD (AUC 0•99), 68 and rapidly progressive AD (AUC 0•99).…”
Section: Tau Proteinmentioning
confidence: 99%
“…• high sensitivity 37,51,52,60 • high specificity versus most neurodegenerative dementias 37,53,54 • moderate specificity versus acute events and encephalitis 63 • low specificity versus atypical AD [54][55][56] • moderate sensitivity for certain sCJD types 51,61 • different cut-offs in the literature 36,[64][65][66] • improved accuracy (p-Tau/t-Tau ratio) 65,67 • prognostic marker 66 • peripheral marker (blood-based) 18,19…”
Section: Taumentioning
confidence: 99%
“…Although a test for in vivo PrP Sc typing is currently unavailable, codon 129 genotyping allows partial patient stratification since early disease onset. In this regard, multivariate analyses adjusted for age and codon 129 genotype showed that CSF and blood NfL, CSF tau, and CSF 14-3-3 were still predictive of survival (Staffaroni et al, 2019;Abu-Rumeileh et al, 2020a;Llorens et al, 2020a). Therefore, current evidence strongly recommends a stratification according to disease subtype or at least codon 129 genotype (in the clinical setting) to select outcomes and endpoints in future clinical trials (Abu-Rumeileh et al, 2020a).…”
Section: Prognostic Valuementioning
confidence: 99%
“…Therefore, they are not yet included in clinical practice. Importantly, the use of surrogate CSF biomarkers is not limited to diagnostic purposes; rather, a potential use as prognostic, predictive, monitoring, and response biomarkers has been proposed [ 35 , 46 , 65 , 71 ]. Therefore, the characterization of the best putative application for each biomarker as well as the identification of biomarkers targeting the complete pathological signatures of prion disease will greatly enhance the rational development and interpretation of future therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%